Thermal limits for the establishment and growth of populations of the invasive apple snail Pomacea canaliculata - Seuffert, Maria Emilia (2017)
Pomacea canaliculata is a South American freshwater snail considered as one of the world’s worst invasive alien species. A temperature of around 25 °C has usually been considered to be optimal for rearing P. canaliculata. Nevertheless, snails have not been reared under a wide range of temperatures to reveal the optimum for performance in terms of population increase. We investigated the effect of temperature on growth, survival and reproduction, estimating demographic parameters for P. canaliculata in the wide range of temperatures at which these snails are active (15–35 °C). No reproductive activity was evidenced for the snails reared at 15 °C, probably explained by the small sizes attained at this temperature. Temperatures above 25 °C did not promote a significant acceleration in growth so higher temperatures will not result in a reduction in time to reach maturity. In fact, snails from 25 and 30 °C began reproduction at the same age. We report here for the first time a detrimental effect of high temperatures that provoked a significant decrease in the contribution of snails to the next generation: the viability of eggs from the snails reared at 30 °C was very low and the snails exposed to a constant water temperature of 35 °C were unable to produce eggs. Our findings reveal a new environmental constraint that could be a determinant of the range limits of this species in invaded regions, especially during the coming decades, anticipating the scenario predicted from global warming.